Grading Religions - Iwasa, Noriaki (Sophia, 2011)
This essay develops standards for grading religions including various forms of spiritualism. First, I examine the standards proposed by William James, John Hick, Paul Knitter, Dan Cohn-Sherbok, and Harold Netland. Most of them are useful in grading religions with or without conditions. However, those standards are not enough for refined and piercing evaluation. Thus, I introduce standards used in spiritualism. Although those standards are for grading spirits and their teachings, they are useful in refined and piercing evaluation of religious phenomena. The spiritual standards complement James’s, Hick’s, Knitter’s, and Netland’s standards. Although most of the spiritual standards are rationally unjustifiable, they have practical value.